Effect of spacing and manuring on growth, yield and nutrient content of Alpinia galanga (L.) Willd. - P Skaria, P P Joy, J Thomas, Samuel Mathew, Baby (Journal of Spices and Aromatic Crops, 2002)
Experiment contected at research farm of the Aromatic and Medicinal Plant Research Station, Odakkali during 1996-1999 to find out the effect of different spacing and manurin on growth, yield and nitrogen, phosphorus and potassium concentration in Alpinia galanga revealed that the optimum spacing for maximum rhizome and oil yield was 40 x 30 cm. Application of FYM at 20 t ha-1 year-1 produced significantly higher rhizome yield, followed by NPK at 100 : 50 : 50 kg ha-1 year-1. Oil recovery was unaffected by these treatments.